Bioinformatics analysis identifies key genes of prognostic value in lung cancer - Dan Song; Li Sun (Journal of Men's Health, 2023)
Lung cancer is the most common human malignancy worldwide and can be divided into different types of carcinomas depending on their pathological features. Advances in medical science and technology have led to the identification of some lung cancer-related marker genes, including EGFR (epidermal growth factor receptor), BRAF (B-Raf proto-oncogene), RAS (RAS proto-oncogene, GTPase) and HER2 (human epidermal growth factor receptor 2). However, the underlying biomarker and key genes associated with different types of lung cancer are still poorly understood. In this study, we analyzed a GEO (Gene Expression Omnibus) dataset and identified 28 upregulated intersection DEGs (different expression genes) and 125 downregulated intersection DEGs among AC (adenocarcinoma), PTC (primary typical carcinoid), PLCC (primary large cell carcinoma), PLCNC (primary large cell lung carcinoma) and PSCLC (primary small cell lung carcinoma). Through PPI (protein-protein interaction) network analysis, we identified 14 genes among the DEGs, namely MFAP4 (microfibril-associated protein 4), PDZD2 (PDZ domain containing 2), FBLN1 (fibulin 1), FBLN5 (fibulin 5), EFEMP1 (EGF containing fibulin extracellular matrix protein 1), KDR (kinase insert domain receptor), S1PR1 (sphingosine-1-phosphate receptor 1), CAV1 (caveolin 1), GRK5 (G protein-coupled receptor kinase 5), EDNRA (endothelin receptor type A), EDNRB (endothelin receptor type B), CALCRL (calcitonin receptor-like receptor), PTGER4 (prostaglandin E receptor 4), and ADRB1 (adrenoceptor beta 1), which were found to be downregulated in different subtypes of lung cancer and associated with poor survival outcomes. In addition, most of the screened DEGs demonstrated good predictive ability in LUAD (lung adenocarcinoma) and LUSC (lung squamous cell carcinoma). Among them, MFAP4 was found to promote cell proliferation while also suppressing cell migration and angiogenesis. In summary, we propose MFAP4, PDZD2, FBLN1, FBLN5, EFEMP1, KDR, S1PR1, CAV1, GRK5, EDNRA, EDNRB, CALCRL, PTGER4 and ADRB1 as potential prognostic markers in lung cancer patients.